(X+1)(x+2) (Х-1)(х-4) (2х-3)(5х-1) (4х-3)(3х+1) Хелп

0 голосов
37 просмотров

(X+1)(x+2)
(Х-1)(х-4)
(2х-3)(5х-1)
(4х-3)(3х+1)
Хелп


Алгебра (17 баллов) | 37 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

(X+1)(x+2)=x²+2x+x+2=x²+3x+2
(Х-1)(х-4)=x²-4x-x+4=x²-5x+4
(2х-3)(5х-1)=10x²-2x-15x+3=10x²-17x+3
(4х-3)(3х+1)=12x²+4x-9x-3=12x²-5x-3

(52.3k баллов)
0 голосов

(х+1)(x+2)=х²+2х+х+2=х²+3х+1
(х-1)(х-4)=х²-4х-х+4=х²-5х+4
(2х-3)(5х-1)=10х²-2х-15х+3=10х²-17х+3
(4х-3)(3х+1)=12х²+4х-9х-3=12х²-5х-3

(7.6k баллов)